Mental Health representations in workers of two specialized institutions of Lima City - Moll León, Sarah (2013)
The exploratory study aims to explore mental health representations in workers of two specialized institutions, through qualitative methodology. A total of ten members of two specialized institutions were selected, five from each, who comprise the interdisciplinary team in the area: A psychiatrist, a psychologist, a nurse, a nursing technician and a social worker. A semi-structured interview was developed to access the speech of the workers. Results show the representational world of the workers, their general conceptions about mental health, the factors that promote or interfere with it, as well as the reactions that a person that suffers mental illness generates, as well as expectations of improvement.